PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT - Charendra, Oktaviana Dian; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTPublic accountants have an obligation to maintain audit quality, it can be determined by two things: thecompetence and the independence. Therefore the aim of this research is to analyze the influence of competenceand independence of the auditor to the audit quality.The population is the entire staff auditor at the PublicAccountant Firm (PAF) in Surabaya. The sample collection technique has been done by using simple randomsampling or simple random which is done by selecting it directly from random population and it has generatedas many as 50 respondents from 10 PAF auditor in the city of Surabaya. The data is the questionnaires whichhave been issued in PAF, this research has been done by using multiple linear regression analysis model.It hasbeen found from the result of the research that the competence and the independence give positive influencetothe audit quality, it shows that when the level of competence and independenceof the auditor is the level of auditquality which has been generated will be high as well.Keywords: Audit quality, competence, independence.